2022
DOI: 10.3389/fneur.2022.807349
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Consensus Weighted Gene Co-expression Network Analysis to Comparative Transcriptome Meta-Datasets of Multiple Sclerosis in Gray and White Matter

Abstract: Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system characterized by demyelination, which leads to the formation of white matter lesions (WMLs) and gray matter lesions (GMLs). Recently, a large amount of transcriptomics or proteomics research works explored MS, but few studies focused on the differences and similarities between GMLs and WMLs in transcriptomics. Furthermore, there are astonishing pathological differences between WMLs and GMLs, for example, there are differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…A correlation network was constructed using the consensus weighted gene co-expression network analysis (cWGCNA) algorithm, a systems biology approach to identify biologically meaningful, co-expression patterns (24, 25). The consensus configuration allows the identification of highly preserved modules, or clusters of interconnected proteins, shared across BA6 and BA37 while retaining region-specific relationships ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A correlation network was constructed using the consensus weighted gene co-expression network analysis (cWGCNA) algorithm, a systems biology approach to identify biologically meaningful, co-expression patterns (24, 25). The consensus configuration allows the identification of highly preserved modules, or clusters of interconnected proteins, shared across BA6 and BA37 while retaining region-specific relationships ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used the consensus Weighted Gene Correlation Network Analysis (cWGCNA; version 1.69) algorithm to generate a central network of co-expression modules from both brain regions (24, 25). The WGCNA::blockwiseConsensusModules function was run with soft threshold power at 7.0, deepsplit of 4, minimum module size of 30, merge cut height at 0.07, mean topological overlap matrix (TOM) denominator, using bicor correlation, signed network type, pamStage and pamRespectsDendro parameters both set to TRUE and a reassignment threshold of 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have explored differences of genetic effects between white and gray matter in MS and have reported the differences at both the proteome 13 and transcriptome levels. 58 , 59 This may be due to the various pathophysiological mechanisms of demyelination in gray and white matter, 60 as white matter lesions are accompanied by activation of local glial cells and infiltration of peripheral leucocytes, whereas gray matter lesions show a lack of activated glial cells and few infiltration of peripheral leucocytes. 61 Another finding was that risk gene dysregulation was associated with the degree of pathological changes, as up‐regulation of SHMT1 could only be observed in macroscopic lesions comparing with healthy controls, but not in NAWM.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that risk gene dysregulation had specificity in distribution, as SHMT1 and FAM120B were significantly up‐regulated in the white matter, while ICA1L was considerably down‐regulated in the gray matter. Several studies have explored differences of genetic effects between white and gray matter in MS and have reported the differences at both the proteome 13 and transcriptome levels 58,59 . This may be due to the various pathophysiological mechanisms of demyelination in gray and white matter, 60 as white matter lesions are accompanied by activation of local glial cells and infiltration of peripheral leucocytes, whereas gray matter lesions show a lack of activated glial cells and few infiltration of peripheral leucocytes 61 .…”
Section: Discussionmentioning
confidence: 99%
“…We used the cWGCNA (version 1.69) algorithm to generate a central network of co-expression modules from both brain regions ( 30 , 31 ). The WGCNA::blockwiseConsensusModules function was run with soft threshold power at 7.0, deepsplit of 4, minimum module size of 30, merge cut height at 0.07, mean topological overlap matrix (TOM) denominator, using bicor correlation, signed network type, pamStage and pamRespectsDendro parameters both set to TRUE and a reassignment threshold of 0.05.…”
Section: Methodsmentioning
confidence: 99%